EFEKTIVITAS ALAT PERMAINAN EDUKATIF (APE) MERONCE BENANG BEKAS TENUN DALAM MENGEMBANGKAN KETERAMPILAN MOTORIK HALUS DAN DAMPAKNYA PADA KEMAMPUAN PRA-MENULIS ANAK USIA 5-6 TAHUN DI TK NEGERI 12 PRAYA TIMUR - Annisa Pujia Astuti; Ida Ermiana; Darmiany (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to find out the effectiveness of the use of Educational Game Tools (APE) using used woven yarn in improving fine motor skills and its impact on the pre-writing ability of children aged 5–6 years in Group B. This research uses a quantitative method with a pseudo-experimental design (Quasi Experimental Design) type One Group Pretest–Posttest. The research subjects consisted of 15 children in group B who were given an initial test (pretest), treatment in the form of meronce activities using used woven yarn for six sessions, and a final test (posttest). The instrument used is in the form of an observation sheet that measures fine motor indicators and pre-writing. The analysis results show that the data is normally distributed so it can be analyzed using the Paired Sample T-Test. In fine motor skills (Y1), the average score increased from 52.86 to 79.13, with a significance value of 0.000 (p < 0.05) and a calculated t value of -24.625, which showed a significant increase after treatment was given. In pre-writing ability (Y2), the average value increased from 50.40 to 77.13 after treatment, with a significance value of 0.000 (p < 0.05) and t calculated -28.488. Based on these results, it can be concluded that the use of APE to use used weaving yarn is effective in improving fine motor skills and has a positive impact on early childhood pre-writing skills. Thus, meronce activities can be used as an alternative learning media that is interesting, environmentally friendly, and suitable to support the development of children aged 5–6 years